Cytogenetic characterization and nuclear DNA content of three North African endemic Centaurea species. (3rd May 2016) - Benamara-Bellagha, M.; Baziz, K.; Pustahija, F.; Khalfallah, N.; Siljak-Yakovlev, S.
Abstract : Three endemic Centaurea species from North Africa are investigated for the first time by chromomycin fluorochrome banding for GC-rich DNA distribution, fluorescence in situ hybridization for physical mapping of rRNA genes, and flow cytometry for genome-size assessment. Investigated species belong to three different sections and possess three basic chromosome numbers: C. tougourensis subsp . tougourensis 2 n = 4 x = 36 ( x = 9), C. musimonum 2 n = 2 x = 20 ( x = 10), and C. maroccana 2 n = 2 x = 24 ( x = 12). The number and distribution of chromomycin positive bands (CMA + ) and 18S-5.8S-26S (35S) rDNA loci were different among investigated species and ranged from 6 to 80 chromomycin bands and from 2 to 6 35S rDNA loci. The three species have just one 5S rDNA locus at intercalary position on a separate chromosome pairs, except in the case of C. musimonum in which both rDNA loci were localized on the same chromosome. All rDNA loci were co-localized with CMA + bands, except three 35S in C. musimonum . Genome size ranged from 2C = 1.66 to 2C = 2.86 pg in diploid species ( C. musimonum and C. maroccana, respectively) and to 2C = 4.51 pg in tetraploid C. tougourensis subsp. tougourensis .